2009
DOI: 10.1152/ajprenal.00404.2009
|View full text |Cite
|
Sign up to set email alerts
|

The farnesoid X receptor modulates renal lipid metabolism and diet-induced renal inflammation, fibrosis, and proteinuria

Abstract: Diet-induced obesity is associated with proteinuria and glomerular disease in humans and rodents. We have shown that in mice fed a high-fat diet, increased renal expression of the transcriptional factor sterol-regulatory element binding protein-1 (SREBP-1) plays a critical role in renal lipid accumulation and increases the activity of proinflammatory cytokines and profibrotic growth factors. In the current study, we have determined a key role of the farnesoid X receptor (FXR) in modulating renal SREBP-1 activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(144 citation statements)
references
References 55 publications
9
132
1
Order By: Relevance
“…The present study demonstrates that the kidney has constitutively high expression of FXR, with a ubiquitous expression pattern along renal tubules, suggesting that FXR may play an important role in renal physiology and pathophysiology. In support, recent studies by Levi Moshe's group have demonstrated that FXR modulates renal lipid metabolism and is involved in the pathogenesis of diabetic nephropathy and represents an attractive therapeutic target for this disease (16,36).…”
Section: Discussionmentioning
confidence: 76%
“…The present study demonstrates that the kidney has constitutively high expression of FXR, with a ubiquitous expression pattern along renal tubules, suggesting that FXR may play an important role in renal physiology and pathophysiology. In support, recent studies by Levi Moshe's group have demonstrated that FXR modulates renal lipid metabolism and is involved in the pathogenesis of diabetic nephropathy and represents an attractive therapeutic target for this disease (16,36).…”
Section: Discussionmentioning
confidence: 76%
“…Also, lower doses of 6-ECDCA have been shown to reduce hepatic and/or plasma cholesterol in apoE Ϫ / Ϫ and Western diet-fed DBA/2J mice ( 56,57 ). It is possible then that the adverse effects associated with the higher dose of 6-ECDCA may have counteracted its potential for reducing plasma cholesterol.…”
Section: Potent Fxr Agonists Decreased Plasma Cholesterol In Ldlr ؊ /mentioning
confidence: 99%
“…FXR inhibits expression of SREBP-1 (Sterol Regulatory Element-Binding Protein 1) and ChREBP (Carbohydrate Response Element-Binding Protein), transcription factors that regulate gene expression of lipogenic and glycolytic enzymes, especially in the liver and adipose tissue (X. Wang et al, 2009). PPAR regulates renal fatty acid -oxidation, preventing at the same time the accumulation of lipids and lipotoxicity phenomenon, and also controls the formation of foam cells (Rigamonti et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…FXR, through the CYP3A11 gene induction, CYP7A1 gene repression, and induction of expression of ileal bile acid binding protein (IBABP), inhibits the biosynthesis of bile acids and increases their transport from the intestine to the liver. High content of FXR in tissues associated with enterohepatic circulation makes it a regulator of drug distribution in the body (Gnerre et al, 2004;X. Wang et al, 2009 www.intechopen.com LXR, after joining the ligand, heterodimerization with RXR and binding of the complex with the promoter of CYP7 gene coding element of steroid 7 -hydroxylase, acts as a 'sensor' of cholesterol concentration, by stimulating its removal from the liver.…”
mentioning
confidence: 99%